Reviving Mung Bean Seeds: The Impact of Hydro Priming and Heat Shock on Germination Rates - Farid, Zabihullah; Amin, Mohammad Wasif; Younisi, Hamidullah; Joya, Khalid; Osmani, Abdul Alim; Amini, Hakimullah (Journal for Research in Applied Sciences and Biotechnology, 2023)
Seed germination is a crucial stage of plant growth that can enhance yield by influencing seedling establishment. The speed and success of germination are key factors that determine the final yield of plants. This research aimed to investigate how hydro priming and heat shock affect the germination properties of green mung bean through a factorial experiment conducted in a completely randomized design with three replications at Parwan University's agronomic laboratory in 2022. The experimental treatments consisted of two temperature levels (35 and 25°C) and three moisture levels (8.5%, 10%, and 11.5%), with four categories of treatment: hydro prim, 30°C shock, 40°C shock, and control. Germination percentage, germination speed, seedling length, and dry weight were measured in the experiment. The results indicated that the triple interaction of temperature, moisture, and treatment was significant only for the germination speed trait at a 5% level. The main effect of temperature and the dual interaction of moisture and treatment at a 1% level were significant for stem length and dry weight. Additionally, the dual interaction between temperature, treatment, and temperature moisture level of 1 and 5% were significant for germination percentage, respectively. Moreover, the study found that hydro priming and thermal flushing treatment frequently improved seed storage capacity. Therefore, the study suggests that hydro priming and heat shock treatments can enhance seed germination and vigor, especially for seed lots stored under unfavorable conditions.